Desain Program Edupreneurship TK Negeri Pembina Pecalungan Kabupaten Batang Edupreuneur dengan Memberdayakan Orangtua dalam Ekosistem Sekolah Melalui Olahan Makanan Berbahan Dasar Singkong - Suryanti, Suryanti (CV. Supernova Office Stationary and Printing, 2023)
Early childhood education is a place for children's growth and development which has many impacts on the lives of children in society later. Early childhood has great potential, so it is necessary to instill character values ??from an early age. The values ??that need to be instilled are the values ??that exist in family, school and community life. One of the important values ??instilled is the value of independence contained in entrepreneurship. In the world of education, entrepreneurship is presented in the form of edupreneurship. Edupreneurship is entrepreneurship education given to children, so they have experience in entrepreneurship activities. The purpose of this research is to develop an edupreneurship program design at Pembina Pecalungan State Kindergarten, Kab. Stem. By getting help from parents in the school ecosystem in processing cassava-based food. The research method used is a class action research method consisting of planning, implementing, supervising, and reflecting. The subjects of this research were the students of TK Pembina Pecalungan, Kab. Stem. The results of this study are to show the application of the edupreneurship program design in TK Pembina Pecalungan, Kab. Batang through parental assistance in managing cassava-based foods.